PELAKSANAAN PENERAPAN RESTORATIVE JUSTICE PADA TAHAP PENUNTUTAN DALAM PERKARA PENGANIAYAAN DI KEJAKSAAN NEGERI SURAKARTA - Muhammad Daffa Athadia; Vincentius Patria Setiawan (Sebelas Maret University, 2023)
This article was written to determine the implementation of the application of restorative justice in solving persecution cases at the prosecution stage. This research is in the form of normative or doctrinal legal research with a case approach, which is prescriptive and applied. The technique of collecting legal materials used in this study is document studies or literature studies obtained from primary and secondary legal materials. The analytical technique used in this study is the deduction syllogism method, which is drawing conclusions using syllogistic logic for legal reasoning derived from legal rules and facts. Based on this research, it was found that there was a compatibility between the termination of prosecution carried out by the Public Prosecutor and Prosecutor's Regulation no. 15 of 2020 concerning the termination of prosecution based on restorative justice. In this case, the suspect NOVYAN PUTRANTO Alias NOVYAN Bin EDY KUSNANTO committed a crime for the first time. The criminal act of persecution committed by the suspect is regulated in article 351 of the Criminal Code with criminal threats regulated in article 1. This case can also be stopped from prosecution based on Article 3 Paragraph 1 of Prosecutor's Regulation no 15 of 2020. The implementation of restorative justice must refer to applicable regulations and the role of the victim who determines the success of the implementation of restorative justice. Keywords: Restorative Justice; Prosecution; Persecution; Application